Protective Effects of Tualang Honey against Oxidative Stress and Anxiety-Like Behaviour in Stressed Ovariectomized Rats - Al-Rahbi, Badriya; Zakaria, Rahimah; Othman, Zahiruddin; Hassan, Asma’; Ahmad, Asma Hayati (Hindawi Publishing Corporation, 2014)
he present study aims to evaluate the antioxidant and anxiolytic-like efect of Tualang honey in stressed ovariectomized (OVX) rats.he animals were divided into; (i) nonstressed sham-operated control rats, (ii) sham-operated control rats exposed to stress, (iii) nonstressed OVX rats, (iv) OVX rats exposed to stress, (v) OVX rats exposed to stress and treated with 17 -oestradiol (E2) (20 g daily, sc), and (vi) OVX rats exposed to stress and treated with Tualang honey (0.2 g/kg body weight, orally). he open ield test was used to evaluate the anxiety-like behaviour and ELISA kits were used to measure oxidant/antioxidant status of the brain homogenates. he result showed that anxiety-like behavior was signiicantly increased in stressed OVX compared to other groups, and administering either E2 or Tualang honey signiicantly decreased anxiety-like behaviour in stressed OVX rats.he levels of malondialdehyde (MDA) and protein carbonyl (PCO) were signiicantly decreased while the levels/activities of superoxide dismutase (SOD), glutathione S-transferases (GST), glutathione peroxidase (GPx), and glutathione reductase (GR) were signiicantly increased in the brain homogenates of treated stressed OVX groups compared to untreated stressed OVX. In conclusion, Tualang honey has protective efects against brain oxidative stress and may be useful alternative anxiolytic agent especially for postmenopausal women.